2002
DOI: 10.1002/ajh.10140
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in hemoglobin SC disease: A four‐decade observational study of clinical, hematologic, and genetic factors

Abstract: Over the past 40 years, we observed 284 subjects with hemoglobin SC disease (Hb SC) for 2,837 person-years. We examined the association of the course of clinical events with hematologic and genetic factors. The mean entry age was 21 years, although 15% entered before one year of age. The mean Hb concentration was 11.3 g/dL, the mean fetal hemoglobin was 2.5%, and the mean MCV was 84.4 fL. Twenty-five subjects died at a median age of 37 years. Chronic organ-specific complications occurred in 112 subjects (39.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 58 publications
(82 reference statements)
6
77
1
7
Order By: Relevance
“…Of 220 SCA patients attended at King Fahad Hospital in a period of 7 years, 16 (7.3%) had AVN. Lower than the prevalence reported by Milner in 1991 (9.8%), and it is far below the more recent studies like the study was done in the USA by Darleen R. Powars which found that (15%) of subjects have AVN, the study in Kuwait by R. Marouf reported an increase in the prevalence to (48.6%), and in London by H. E. Ware the prevalence reached (41%) [15,21,17,22]. The recent studies claim that this increase in prevalence is due to advancement of diagnosis and radiological imaging.…”
Section: Discussion:-contrasting
confidence: 42%
“…Of 220 SCA patients attended at King Fahad Hospital in a period of 7 years, 16 (7.3%) had AVN. Lower than the prevalence reported by Milner in 1991 (9.8%), and it is far below the more recent studies like the study was done in the USA by Darleen R. Powars which found that (15%) of subjects have AVN, the study in Kuwait by R. Marouf reported an increase in the prevalence to (48.6%), and in London by H. E. Ware the prevalence reached (41%) [15,21,17,22]. The recent studies claim that this increase in prevalence is due to advancement of diagnosis and radiological imaging.…”
Section: Discussion:-contrasting
confidence: 42%
“…Specifically, Hb SC has a milder clinical course relative to homozygous SCD which is characterized by fewer vaso-occlusive events, a less intense hemolytic anemia, less frequent priapism, and a nearly normal average lifespan [2,6,33]. However, some vaso-occlusive manifestations including retinopathy and osteonecrosis may be more frequent in SC disease [34,35]. A similar protective association with pulmonary hypertension is also likely to be present in Sb 1 thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 69% of foreign born patients, the mean duration of residence in France was 13.8 years and the mean duration of follow up at the center was 5.1 years. Fifty-eight percent of female patients had been pregnant with a mean of 1.9 children per woman and 32 spontaneous abortions were reported in 12 females (5 multiple abortions, range [2][3][4][5][6][7][8][9][10][11]. High body mass index (≥25kg/m 2 ) and blood hypertension (> 130/80 mmHg) were reported in 33% and 14% of HbSC patients, respectively.…”
Section: Demographic Findingsmentioning
confidence: 99%
“…5 Curiously, whereas SCA clinical features have been extensively studied, very few studies have been dedicated specifically to HbSC disease. 3,[6][7][8][9] Indeed, HbSC disease is generally considered to be a variant of SCA, sharing similar clinical complications though with a milder severity and a lower frequency. 7 Therefore, the aim of our study was to examine the specific clinical and biological features of HbSC disease in a single center patient cohort.…”
Section: Introductionmentioning
confidence: 99%